Vaping, Demographic Characteristics and Dry Mouth Complaints on Consumers Bejo Vape Store Jember - Kiswaluyo Kiswaluyo; Surartono Dwiatmoko; Sulistiyani Sulistiyani; Ahmad Yarham (Humanistic Network for Science and Technology (HNST), 2022)
A vape or e-cigarette is a battery-powered inhaler that serves nicotine which the WHO calls the Electronic Nicotine Delivery System (ENDS). Vape is a technology that resembles tobacco cigarettes without burning the tobacco leaves. Metal casing with built-in battery-powered atomizer to generate steam to inhale from cartridges containing propylene glycol and glycerol, flavorings, and nicotine. Various studies have been carried out to determine the impact of vaping. This study aims to determine the correlation between vaping with demographic characteristics and dry mouth complaints. The design of this study was cross-sectional, involving 44 people aged less than 60 years, who were selected using a purposive sampling technique. Data were collected by filling out questionnaires and saliva examination, then analyzed using Fisher's exact test and Spearman's correlation. Based on the results of the study it can be concluded that smoking vaping has an correlation with dry mouth complaints (dry mouth complaints score and salivary secretion rate) and age. Keywords: vaping; dry mouth complaints; demographic characteristics